Noncoding Sequences Conserved in a Limited Number of Mammals in the SIM2 Interval are Frequently Functional - Frazer, Kelly A.; Tao, Heng; Osoegawa, Kazutoyo; de Jong, Pieter J.; Chen, Xiyin; Doherty, Mark F.; Cox, David R. (Genome Research, 2004)
Cross-species DNA sequence comparison is a fundamental method for identifying biologically important elements, because functional sequences are evolutionarily conserved, wheres nonfunctional sequences drift. A recent genome-wide comparison of human and mouse DNA discovered over 200,000 conserved noncoding sequences with unknown function. Multispecies DNA comparison has been proposed as a method to prioritize these conserved noncoding sequences for functional analysis based on the hypothesis that elements present in many species are more likely to be functional than elements present in limited numbers of species. Here, we perform a comparative analysis of the single-minded 2 (SIM2) gene interval on human chromosome 21 with horse, cow, pig, dog, cat, and mouse DNA. We classify conserved sequences based on the number of mammals in which they are present, and experimentally test sequences in each class for function. As hypothesized, conserved sequences present in many mammals are frequently functional. Additionally, we demonstrate that sequences conserved in a limited number of mammals are also frequently functional. Examination of genomic deletions in chimpanzee and rhesus macaque DNA showed that several putatively functional conserved noncoding human sequences were absent in these primates. These findings suggest that functional conserved noncoding human sequences can be missing in other mammals, even closely related primate species.